The Influence of Brand Image on Purchase Decisions for OMG Cosmetics Among Millennial Consumers Aged 27-42 - Zikri Fachrul Nurhadi; Adzkia Safitri Anggraeni (Sinergi International Journal of Management and Business, 2026)
This study analyzes the influence of Brand Image on Purchase Decisions of OMG (Oh My Glam) cosmetics among Millennials. The Indonesian cosmetics industry, which is growing by 21.9%, creates intense competition that requires brands to build a strong image to influence consumer behavior. The main problem studied is how perceptions and associations of the OMG brand drive purchase decisions in the vast digital market. The purpose of this study is to measure the extent to which Brand Image has a significant influence on Purchase Decisions for Millennial consumers. The novelty of this study lies in its focus on challenger brands in the digital era, going beyond previous studies that only measure brand awareness to measure actual purchase actions. This study uses a quantitative approach with deductive reasoning and a foundation of David A. Aaker's Brand Equity Theory. Data were collected through the bold distribution of questionnaires to millennial consumers to test the causal relationship between variables. The results of this study indicate that a positive and strategic brand image significantly improves purchase decisions, as evidenced by the inclusion of OMG in the list of 10 best-selling brands on Shopee and Tokopedia. The conclusion of this study shows that brand image significantly influences the purchasing decisions of OMG (Oh My Glam) cosmetic products among millennial consumers aged 27–42 years. A strong brand image, including perceptions of quality, trustworthiness, and lifestyle suitability, can increase consumer interest and confidence in purchasing the product. Millennial consumers tend to choose OMG because the brand is perceived as relevant, modern, and represents their identity.